2020
DOI: 10.21018/rjcpr.2020.1.290
|View full text |Cite
|
Sign up to set email alerts
|

This time is different. The globalization of uncertainty

Abstract: “Some warn that the disease will be remembered not only as a human catastrophe, but also as a geopolitical turning-point away from the West. Are they right?” (Minton Beddoes, 2020). Irrespective of the answer, this question raises the unsettling issue of the viability of the current international order. This is not a singular voice. For instance, Henry Kissinger unequivocally asserts that “The coronavirus pandemic will forever alter the world order” (Kissinger, 2020). Analyses focusing on the geopolitical impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The interval between the appearance of the first case between China and the United States was one month. According to the Lancet's research on January 24, 2020, the first confirmed patient with novel coronavirus pneumonia became ill on December 1, 2019 [19]. After a preliminary understanding of the symptoms and response measures of the novel coronavirus, the Chinese government quickly informed the World Health Organization of the novel coronavirus pneumonia on December 31, 2012 [20].…”
Section: Discussionmentioning
confidence: 99%
“…The interval between the appearance of the first case between China and the United States was one month. According to the Lancet's research on January 24, 2020, the first confirmed patient with novel coronavirus pneumonia became ill on December 1, 2019 [19]. After a preliminary understanding of the symptoms and response measures of the novel coronavirus, the Chinese government quickly informed the World Health Organization of the novel coronavirus pneumonia on December 31, 2012 [20].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of the pandemic on the global economies were sharp and dramatic. “We are currently experiencing a deep economic and financial crisis, the sharpest downturn in the global economy since the Great Depression of the 1930s” [ 29 , p. 46] (see also [ 31 , p. 129]). Wullweber [ 29 , p. 2 ] notes that “the nature of the COVID-19 crisis is exceptional: It has triggered a demand-side as well as a supply-side shock”.…”
mentioning
confidence: 99%
“…Debt growth as a result of economic and financial disruption caused by the COVID-19 pandemic is also a major source for concern among governments, businesses and individuals. For example, the IMF forecast that global gross government debt would increase by US$6 trillion, which means the debt increases from 105 to 122% of GDP [ 31 , p. 129]. The concern caused by the growing government, corporate and private debt as a result of the pandemic has featured in numerous media reports around the globe.…”
mentioning
confidence: 99%